Designing probiotics with respect to the native microbiome. (May 2012) - Barzegari, Abolfazl; Saei, Amir Ata
It is now well known that genetic and environmental factors affect the intestinal microbiome in an individual's lifetime and thus, different individuals possess different intestinal microbiomes and microbial metabolomes. The intestinal microbiome has been shown to differ among individuals from the same sex, between sexes and between individuals of different ages. Different families and, from a larger perspective, different communities, possess different microbiomes, and thus corresponding metagenomes. Therefore, it can be deduced that each individual human being can be characterized by his/her own intestinal microbial fingerprint. This understanding may prove helpful in future individualized medicine. These microorganisms are natural beneficial symbionts of the GI tract, have adapted to their human host over million years of coevolution and are now regarded as the second human genome. The difference in intestinal microbiome of different populations may explain why the results from different clinical trials on probiotic efficacy do not match with each other. People pay much, but they benefit little. In this article, it is recommended to isolate probiotics from natives' microbiomes and in the interest of efficacy, to use them in the same population. This line of thought can be considered in future guidelines from the Food and Agriculture Organization and the WHO on evaluation of probiotics in foods.